2011
DOI: 10.1128/jvi.01112-10
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Saliva Causes Enhancement of West Nile Virus Infection in Mice

Abstract: West Nile virus (WNV) is transmitted to vertebrate hosts primarily by infected Culex mosquitoes. Transmission of arboviruses by the bite of infected mosquitoes can potentiate infection in hosts compared to viral infection by needle inoculation. Here we examined the effect of mosquito transmission on WNV infection and systematically investigated multiple factors that differ between mosquito infection and needle inoculation of WNV. We found that mice infected with WNV through the bite of a single infected Culex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(193 citation statements)
references
References 31 publications
(57 reference statements)
6
179
0
1
Order By: Relevance
“…However, the viremia developing in mallards was two logs higher than peak viremia in either Wood Ducks or Aigamo Ducks and may have been due to greater susceptibility of mallards to WNV or to enhancement of WNV infection by mosquito saliva, which has been reported in experimentally infected mice (Schneider et al 2007;Styer et al 2011) and chickens (Styer et al 2006). The proportion of Wood Ducks that shed WNV orally is similar to the range of oral shedding of WNV in Aigamo Ducks; however, Aigamo Ducks shed 1-2 logs more WNV.…”
Section: Discussionmentioning
confidence: 86%
“…However, the viremia developing in mallards was two logs higher than peak viremia in either Wood Ducks or Aigamo Ducks and may have been due to greater susceptibility of mallards to WNV or to enhancement of WNV infection by mosquito saliva, which has been reported in experimentally infected mice (Schneider et al 2007;Styer et al 2011) and chickens (Styer et al 2006). The proportion of Wood Ducks that shed WNV orally is similar to the range of oral shedding of WNV in Aigamo Ducks; however, Aigamo Ducks shed 1-2 logs more WNV.…”
Section: Discussionmentioning
confidence: 86%
“…Studies comparing subcutaneous inoculation and mosquito transmission of WNV have demonstrated that mosquito saliva can promote the generation of higher viremia early in infection in mice and newly hatched birds, reduce the time taken for the virus to enter the CNS, and elicit higher mortality rates [149,166,167]. Mosquito saliva has been shown to modulate immune cell infiltration at the site of inoculation and reduce the expression of Th1 cytokines and TLR3 [150,174].…”
Section: The Contribution Of the Route Of Inoculation And Virus Dose mentioning
confidence: 99%
“…Since capillary-feeding mosquitoes discharge virus-laden saliva into the dermis during probing as well as into the blood during feeding, most studies utilize subcutaneous injection to experimentally mimic the natural route of infection. Subcutaneous co-inoculation of virus with mosquito saliva has also been employed by some groups to imitate natural infection [168].…”
Section: The Contribution Of the Route Of Inoculation And Virus Dose mentioning
confidence: 99%
“…Mosquitoes are important vectors of numerous infectious diseases of humans, including malaria (Mitri and Vernick 2012), dengue fever (Jeffery et al 2009), yellow fever (Barrett and Higgs 2007), West Nile fever (Styer et al 2011), encephalitis, and filariasis (Gambhir andMichael 2008, Smith et al 2008). The chemical control of mosquitoes, via the use of insecticides, is the primary means of managing the spread of these diseases, as it is simple, rapid, and economical , Mahande et al 2012.…”
mentioning
confidence: 99%